Sustaining India’s rapid rise as a major refined product exporter - Bose, N (Oxford Institute for Energy Studies, 2015)
Over the last decade, India has evolved into the world’s seventh-largest exporter of refined petroleum products. According to the US Energy Information Administration (US-EIA), India’s refining capacity almost doubled during this period to about 4.35 million barrels/day (mb/d) at the end of 2013, making India the second-largest refiner in Asia after China, and the world’s fifth largest. According to the 2014 BP Statistical Review, in 2013, India imported 269,000 mb/d of petroleum products, and exported roughly 1.24 mb/d, making it the largest product exporter in Asia. It has been a net exporter of refined products since 2001.